OPTIMIZING TRANSPORTATION SYSTEMS AND MITIGATING RISKS: A COMPREHENSIVE ANALYSIS OF DISTRIBUTION SUPPLY CHAIN CHALLENGES - Imane BENALLOU; Abdelah AZMANI; Monir AZMANI; Mouna ATIK EL FTOUH (Scientific Journal of Silesian University of Technology. Series Transport)
The effectiveness of the transportation system aids in the successful economic development of any nation, as studies by foreign scientists have shown that road transport is one of the most critical contributors to budget revenue. Nevertheless, the quality of the products and services offered to the end user affects any company's reputation, market share, and financial stability. Being proactive is essential to ensuring low-risk impact, which entails developing a risk management plan to support the operation through well-defined policies and practices. On the one hand, the company will thus be able to differentiate itself in an often competitive market by implementing an effective shipping protocol that considers and plans risks; on the other hand, it will guarantee its customers a timely delivery, as planned. This article focuses on the various problems affecting the distribution supply chain and the negative consequences for the company's image and financial performance.